Integrated Project Management at State-Owned Enterprise Holding Survey Services - Budi Prakoso; Rachma Fitriati (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
An ongoing challenge in BKI's project management is the frequent delays in project completion and mismatch of current targets. This article aims to analyze the integrated project management system, digitalization, and the concept of digital governance at PT. Biro Klasifikasi Indonesia (BKI) as the parent company of the State-Owned Enterprise (SOE) Holding Survey Services (IDSurvey). The study used qualitative methods with five dimensions of project efficiency, team satisfaction, impact on customers, business success, and preparing for the future. The results showed that although BKI has planned various business strategies, a strong commitment is needed to resolve project management issues through improved integrated digital governance. This study recommends resolving project management issues through improved integrated project success.